Production Facility Layout Design Using Activity Relationship Chart (ARC) And From To Chart (FTC) Methods - Ata Barbara; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2021)
XYZ is a company engaged in the field of transformers which produces several types of transformers. Transformer production process is made to order a production process that has a fluctuating pattern. Companies also often cannot estimate the number of transformers that will be produced to meet consumer demand. The purpose of this study is to improve plant layout with an efficient layout. One method used in this study is the Activity Relationship Chart and From To Chart methods. Activity Relationship Chart and From To Chart are methods that can help solve problems which are then explained in more detail through several stages of completion to the optimal point. This research is expected to produce a more efficient layout using the Activity Relationship Chart and From To Chart method.